The effect of tracheotomy on ventilator-associated pneumonia rate in children. (May 2020) - Topal, Sevgi; Demir, Emine; Atakul, Gülhan; Çolak, Mustafa; Soydan, Ekin; Karaarslan, Ünal Utku; Yaşar, Nevbahar; Kıymet, Elif; Devrim, İlker and Ağın, Hasan
Abstract: Objectives: Data on the relationship between tracheotomy and ventilator-associated pneumonia (VAP) in children is very limited. We planned to evaluate the effect of tracheotomy on VAP rates in children. Materials and methods: We evaluated patients who underwent tracheotomy during follow-up at the pediatric intensive care unit (PICU) of our hospital. Patients who were diagnosed as VAP at least once and followed by a mechanical ventilation (MV) for at least 30 days before and after tracheotomy were included in our study. The underlying diagnoses of the patients and the number of VAP diagnosis, VAP rates (VAP number x1000/day of MV) before and after tracheotomy were recorded. Logistic regression analysis was used to compare VAP rates before and following a tracheotomy. Results: There were a total of 47 patients including 28 (59.6%) girls and 19 (40.4%) boys in our study. The duration of MV before tracheotomy was 74.9 ± 48.9 (31–295) days and after tracheotomy, it was 103.3 ± 102.8 (30–586) days. The number of VAP before tracheotomy was 0.9 ± 1.2 (0–8) and after tracheotomy, it was 0.6 ± 0.6 (0–3). The VAP rate before tracheotomy was 5.9 ± 6.3 (0–26.5) and the VAP rate after tracheotomy was 3.2 ± 3.8 (0–11.4). Ventilator-associated pneumonia rates were lower following tracheotomy (OR:0.91, 95%CI:0.826–0.981, p = 0.017). Conclusion: Tracheotomy decreased the VAP rate in children receiving long-term mechanical ventilatory support.